The Development of Animated Video Media in Mathematics Learning Map Scale Material for Grade V Elementary School Students - Pramesti, Mutiara; Amelia, Winda (Bulletin of Pedagogical Research, 2022)
This study aims to develop animated video learning media that has a level of validity and attractiveness so that it can be used to increase students' interest in learning mathematics on a map scale material for class V Elementary School, determine the effectiveness of the media, and determine student responses to the use of the media. This research is a type of Research and Development (RnD) research or research and development according to Borg and Gall, which consists of: (1) research and data collection, (2) planning, (3) product design, (4) product design validation. (5) product revision, (6) product trial, (7) usage trial. The subjects of the trial in this study were the fifth grade students of SDN Cikoko 03, South Jakarta, totaling 32 students with details of 9 students being tested on a small scale, and 32 students being tested on a large scale. The results of this study indicate the level of validity of animated video learning media as learning media based on assessments by media experts, material experts, and language experts. Keyword : Development Learning Media, Animated Video, Map Scale Material